Patient Safety Culture and Its Associated Factors Among Perioperative Staff in the Operating Theater at Sarawak General Hospital - Yi Lin, Bong (Universiti Malaysia Sarawak, 2024)
Patient safety is a fundamental concern in healthcare, especially in high-risk settings such as operating theaters, where there is an increased likelihood of adverse events. Nonetheless, local studies within the operating theater setting remain limited, particularly those addressing the complex interplay between active and latent failures. This study examined the influence of organizational and individual factors, and the moderating effects of job position, gender, and years of experience toward patient safety culture among perioperative staff at Sarawak General Hospital (SGH) in Malaysia. A cross-sectional study was employed, involving 137 perioperative staff members, including both doctors and nurses, selected through convenience sampling. The Safety Attitude Questionnaire-Operating Room (SAQ-OR) and Hospital Survey on Patient Safety Culture (HSOPSC) was adapted in this study. The responses were analyzed via descriptive analysis and partial least square-structural equation modeling (PLS-SEM). Most respondents (67.2%) were registered nurses. The stress recognition dimension had the highest mean positive response rate at 73.0%, whereas the perceptions of management dimension had the lowest at 22.6%. The study findings revealed a significant positive relationship between individual factors and the perception of patient safety culture. In contrast, the association between organizational factors and the perception of patient safety culture was positive but not significant. The moderating effects of position, gender, and years of experience in a specialty were also non-significant. Overall, the perception of patient safety culture in the Sarawak General Hospital (SGH) operating theater was rated as good. The lowest positive response rate in the management dimension implies the need for the organization to address staffing shortage issues and improve workplace support to increase patient safety. Individual factors, such as job satisfaction and stress recognition, significantly influence these perceptions. Improving these aspects through supportive policies and management interventions is necessary to enhance safety culture. With a coefficient of determination (R²) value of 42.6% in this structural model, additional influencing factors may be relevant. Future studies should explore influences such as government policies, budget allocation, and technological advancements to further enhance patient safety culture in operating theaters.